الشخصية بين النموذج المناضل والمضاد في رواية (خطوات في الاتجاه الآخر) لحفناوي زاغز - فورار, أمحمد بن لخضر; بدري, ربيعة (Revues faculté des lettres et des langues; Vol. 1 No 21 (2017): مجلة كلية الآداب و اللغات, 2018)
ABSTARCT: This paper aims at exploring a number of archetypal patterns of fictional characters in Lehafnoui Zaghez’s novel Steps on the other Direction. On one hand, there is the archetype of the political activist, the novel’s protagonist, who campaigns for the recovering of usurped human rights. On the other hand, one may detect the opposite archetypal character, i.e. the antagonist. The latter is a character who hampers and stands against the protagonist’s efforts and desires. In fact, this archetype of character is embodied by the terrorist organisation in the novel. الملخص   يهدف هذا المقال إلى التعرف على بعض نماذج الشخصيات الروائية، وذلك في رواية "خطوات في الاتجاه الآخر" لحفناوي زاغز ، فكان هناك نموذج المناضل الذي يكافح و يدافع عن حقوق الإنسان المهضومة وتمثل في بطل الرواية. والنموذج المضاد الذي يعد الشخصية المناوئة والمضادة التي تعرقل رغبة ومسار الشخصية المناضلة، وتمثل في الرواية في المنظمة الإرهابية.